Sosialisasi Sekolah Ramah Anak Pada MAN Malakaji di Kabupaten Gowa Sulawesi Selatan - Najamuddin Najamuddin; Bustan Bustan; Hasni Hasni (Universitas Negeri Makassar, 2020)
This Community Partnership Program (PKM) partner is the Socialization of Child Friendly Schools in MAN Malakaji, Gowa Regency, South Sulawesi. The problems are: (1) The stakeholders' lack of awareness to work together to create child-friendly schools. (2) Teachers still do not understand in detail the concepts and programs of Child-Friendly Schools, so their implementation is still not effective. The methods used are: lectures, demonstrations, discussions, questions and answers with colleagues through the Zoom Meeting application. The results achieved were (1) partners were very enthusiastic about the socialization, marked by the number of participants and questions asked, (3) partners really needed socialization and understanding of Child Friendly Schools which was shown by the spirit of participation and curiosity, (4) Quality improvement understanding and mastery is ensured. contrary to the concept of the Child-Friendly School Program (SRA).